2020
DOI: 10.1108/ijlma-03-2018-0044
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the factors affecting probable failure of local entrepreneurs

Abstract: Purpose This study aims to investigate and analyze the factors affecting the probable failure of rural entrepreneurs so that the most important factors responsible for failure in the business of small and local entrepreneurs are identified. Design/methodology/approach The present survey was conducted through the descriptive-analytical method by using a researcher-made questionnaire. The statistical population of the study included 1,641 greenhouse owner entrepreneurs in five rural communities. To clarify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The concepts such as motivations, individual skills and human capital are subtopics of psychological traits. Qeidari et al (2020) concluded that individual and managerial skills are among the priorities in clarifying factors affecting probable failure of greenhouse businesses. Ataei et al (2020) analyzed entrepreneurial competencies (including entrepreneurial vigilance, networking ability, individualism, tolerance of ambiguity and market analysis) required for launching enterprises by rural youth.…”
Section: Rural Entrepreneurship Literaturementioning
confidence: 99%
“…The concepts such as motivations, individual skills and human capital are subtopics of psychological traits. Qeidari et al (2020) concluded that individual and managerial skills are among the priorities in clarifying factors affecting probable failure of greenhouse businesses. Ataei et al (2020) analyzed entrepreneurial competencies (including entrepreneurial vigilance, networking ability, individualism, tolerance of ambiguity and market analysis) required for launching enterprises by rural youth.…”
Section: Rural Entrepreneurship Literaturementioning
confidence: 99%